The Bridge Over the Lake: Spanning Across Lake Maracaibo in Venezuela - Gómez, Hannia; Montiel, Rino (Docomomo Journal, 2011)
The General Rafael Urdaneta Bridge spanning over Lake Maracaibo in Venezuela (1958–1962), designed by Ing. Professor Riccardo Morandi, a masterpiece of Modern engineering, is now a Modern Landmark at Risk. The remarkable and little known story of the construction of this structure “could not be accomplished by a handful of men. From planning to financing, from design to construction, a great number of Venezuelan and European engineers worked jointly in Wiesbaden, Caracas, Rome, Maracaibo, Zürich, Paris, and Lisbon. In this way, one of the most outstanding structures of our time was erected within the stipulated - and brief construction time.”